2021
DOI: 10.1037/dhe0000169
|View full text |Cite
|
Sign up to set email alerts
|

Student–faculty interactions and psychosociocultural influences as predictors of engagement among Black college students.

Abstract: While engagement has been identified as a key component to enhancing the academic outcomes of college students, less work has focused on specific predictors of engagement for Black college students attending predominately White postsecondary institutions (PWIs). The current study examined the influence of 2 dimensions of student-faculty interactions (caring attitudes and respectful interactions) and psychosociocultural factors (racial identity, perceptions of the university environment, and cultural congruity)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
(134 reference statements)
0
15
0
Order By: Relevance
“…Given that much of the research using the PSC framework has primarily focused on the relationship between PSC factors and the persistence attitudes of students of color at PWIs (Gloria & Castellanos, 2003;Gloria et al, 1999), this study extends the literature using the PSC framework in multiple ways. It adds to the limited empirical research in this area by focusing specifically on Black students rather than on students of color broadly (e.g., Beasley, 2020;Gloria et al, 1999). Furthermore, consistent with calls for more research on noncognitive PSC variables among college students of color (Sedlacek, 2017), this study highlights multiple noncognitive predictors that can facilitate Black students' academic functioning and performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that much of the research using the PSC framework has primarily focused on the relationship between PSC factors and the persistence attitudes of students of color at PWIs (Gloria & Castellanos, 2003;Gloria et al, 1999), this study extends the literature using the PSC framework in multiple ways. It adds to the limited empirical research in this area by focusing specifically on Black students rather than on students of color broadly (e.g., Beasley, 2020;Gloria et al, 1999). Furthermore, consistent with calls for more research on noncognitive PSC variables among college students of color (Sedlacek, 2017), this study highlights multiple noncognitive predictors that can facilitate Black students' academic functioning and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Black students who reported higher cultural congruity, endorsed more support from faculty mentors, and had more positive views of campus were more likely to persist. Beasley (2020) found that cultural congruity, perceptions of the university environment, and caring faculty relationships were significant predictors of Black students' academic and social engagement attitudes.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
See 2 more Smart Citations
“…While some prior research has investigated race and student-faculty interactions, we have much to learn about the moderating effects of race and ethnicity related to these experiences. A recent study examining 209 Black students at a large Southwestern predominately White institution (PWI) found a positive link between student-faculty interactions and academic and social engagement (Beasley, 2020). Additionally, one prior qualitative study of African American college students suggested student-faculty interactions may promote perceptions of racism, bias and microaggressions in students, resulting in negative perceptions of the campus climate (Solorzano et al, 2000).…”
Section: Student-faculty Interactionsmentioning
confidence: 99%